A systematic review of the literature on work engagement and learning agility in increasing Generation Z employee loyalty - Hanim, Syarifah; Ringko, Awang; Sahrah, Alimatus (Universitas Tanjungpura, 2025)
This study conducts an in-depth exploration of work engagement and learning agility contributions in strengthening Generation Z employee loyalty through a systematic literature review approach covering the 2021-2025 publication period. The Systematic Literature Review (SLR) methodology with PRISMA protocol was applied to analyze 13 peer-reviewed journal articles extracted from academic repositories including Scopus, Web of Science, and Google Scholar. Selection criteria encompassed empirical publications exploring a minimum of two out of three core variables with a focus on samples or specific discussions regarding Generation Z characteristics. Findings indicate that work engagement, particularly in the emotional engagement aspect, demonstrates significant dominance in Gen Z employee retention with a coefficient value of β = 0.68. Learning agility is identified as playing a mediating mechanism role that connects organizational capabilities with manifestations of workforce innovative behavior. Gen Z loyalty characteristics are conditional and value-oriented, with primary determinants including job satisfaction, work-life balance, work motivation, and employer branding. Holistic integration of both constructs reveals effectiveness superiority compared to conventional paradigms. The research produces a Generational Loyalty Framework that underscores purpose-driven work, emotional connection, and continuous learning as essential foundations of Gen Z loyalty. Applicative implications encompass formulation of meaningful engagement strategies, development of experiential learning-based agility programs, and adoption of flexible work arrangements to optimize digital era talent retention